Numerical methods: a programming-based approach - Jalan, Arun Kumar (Universities Press, 2015)
Numerical methods: a programming-based approach / Jalan, Arun Kumar. -- Kolkata: Universities Press, 2015 515 J26 No. of Copies : 2